2017
DOI: 10.3892/mco.2017.1234
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survival in Qidong between 1972 and 2011: A population-based analysis

Abstract: Abstract. Population-based cancer survival is an improved index for evaluating the overall efficiency of cancer health services in a given region. The current study analysed the observed survival and relative survival of leading cancer sites from a population-based cancer registry between 1972 and 2011 in Qidong, China. A total of 92,780 incident cases with cancer were registered and followed-up for survival status. The main sites of the cancer types, based on the rank order of incidence, were the liver, stoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…Moreover, the subgroup analysis showed that, compared with the Caucasian populations, the test had better ability to detect bladder cancer in Asian populations. Considering the increasing incidence of bladder cancer in Asian countries, the NMP22 BladderChek test should be promoted for bladder cancer detection and follow-up [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the subgroup analysis showed that, compared with the Caucasian populations, the test had better ability to detect bladder cancer in Asian populations. Considering the increasing incidence of bladder cancer in Asian countries, the NMP22 BladderChek test should be promoted for bladder cancer detection and follow-up [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most commonly diagnosed and deadly malignant tumors worldwide [1] . HCC was still one of the most cancers in the inshore area of Yangtze River, China, due to hepatitis B virus (HBV) infection-related chronic hepatitis or liver cirrhosis [2] . There have been no more effective therapeutic options in the advanced HCC beyond sorafenib or a multi-targeted tyrosine kinase inhibitors, because hepatic hypoxia enhances cell proliferation, angiogenesis, and suppresses differentiation and apoptosis leads to resistance of transarterial chemoembolization (TACE) [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common or deathly human malignancy cancers worldwide [1,2] , especially in the areas along the Yangtze River. Recently, Chen et al [3] reported the observed survival and relative survival of leading cancer sites from a population-based cancer registry for 40 years. The main sites of the cancer types with a total of 92,780 incident cases in Qidong, China, HCC ranks the first based on the rank order of incidence among all malignancies (liver, stomach, lung, colon and rectum, oesophagus, breast, pancreas, leukaemia, brain and central nervous system, bladder, non-Hodgkin's lymphoma, and cervix) and the poorest survival rate [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chen et al [3] reported the observed survival and relative survival of leading cancer sites from a population-based cancer registry for 40 years. The main sites of the cancer types with a total of 92,780 incident cases in Qidong, China, HCC ranks the first based on the rank order of incidence among all malignancies (liver, stomach, lung, colon and rectum, oesophagus, breast, pancreas, leukaemia, brain and central nervous system, bladder, non-Hodgkin's lymphoma, and cervix) and the poorest survival rate [3] . The leading etiological factors of HCC include chronic hepatitis B or C virus (HBV [4][5][6] or HCV [7,8] ) infection, aflatoxin contaminated food taken and non-alcohol fat liver diseases (NAFLD) [9,10] .…”
Section: Introductionmentioning
confidence: 99%